COMPARATIVE STUDY OF NUTRITIONAL STATUS OF PRIMARY SCHOOL CHILDREN IN URBAN AREA OF JHANSI - Singh, Ranjana; Bhatnagar, M; Mathur, B P; Singh, Hemant; Kr, Yogesh (Indian Journal of Community Health, 2010)
The present study is an attempt to find out the nutritional status including anthropometric assessment. A cross -sectional study was conducted in primary section of two governments and Iwo convent schools of Jhansi city during the study period of march 1999 to feb2000.Selected school children (n=840) aged 5-11 years, 453 children from municipal school and 387 children from convent school comprised the study material. Following results were observed -out of total children surveyed, 52.98% were male and rests 4 7.02% were females. Hindu formed majority (70.90%) of children in both types of schools. Mean height and weight of boys and girls were higher than ICMR standards in both type of school. The mean mid arm circumference of all girls and boys from both type of schools had higher value than the ICMR standards but did not come up to WOLANSKI standard. Statistical analysis-percentage, mean, chi-square test.